2019
DOI: 10.1111/dom.13619
|View full text |Cite
|
Sign up to set email alerts
|

Largest single‐centre experience of dulaglutide for management of diabetes mellitus in solid organ transplant recipients

Abstract: Published data regarding the approach to management of diabetes mellitus in solid organ transplant (SOT) recipients are limited. We performed a retrospective chart review of SOT recipients with diabetes, above 18 years of age, who were usisng dulaglutide. There was a sustained, statistically significant reduction in the primary endpoints of weight, body mass index (BMI) and insulin requirement in 63 SOT recipients at 6, 12 and 24 months, respectively. A total of 59, 50 and 13 recipients were followed during 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 12 publications
(33 reference statements)
3
60
0
8
Order By: Relevance
“…Our data shows that GLP-1RA improved glycemic control, with improvements in HbA1c (-0.75%) and decreases in total daily dose of insulin (16.25 units) 12 months from baseline in SOT recipients. The number of oral medications decreased with GLP-1RA initiation, similar to results reported by Singh et al [12]. We saw reductions in weight and BMI in our cohort by a mean of 4.86 kg and 1.63 kg/m 2 , respectively, at the end of 12 months.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data shows that GLP-1RA improved glycemic control, with improvements in HbA1c (-0.75%) and decreases in total daily dose of insulin (16.25 units) 12 months from baseline in SOT recipients. The number of oral medications decreased with GLP-1RA initiation, similar to results reported by Singh et al [12]. We saw reductions in weight and BMI in our cohort by a mean of 4.86 kg and 1.63 kg/m 2 , respectively, at the end of 12 months.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to those of Pinelli et al [11], who reported a small case series of five patients that received co-administration of liraglutide with tacrolimus post kidney transplant; liraglutide did not clinically affect the trough tacrolimus levels. Singh et al [12] also reported in their study of dulaglutide in SOT recipients that the immunosuppressant regimen remained stable without any increased dose adjustment. This is in contrast to the Liou et al [10] study of five patients on liraglutide after kidney transplant, who reported that three patients could reduce the dose of tacrolimus and maintain optimal therapeutic levels.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Given their glucose‐lowering ability, decreased risk of hypoglycemia and minimal drug interactions, they are widely used in the general population. A few retrospective studies, including one from our research group, have demonstrated the safety and effectiveness of GLP‐1 analogues in SOT . Some studies have compared the various GLP‐1 analogues in a general population, but, to date, there have been no comparative studies in the SOT population .…”
Section: Introductionmentioning
confidence: 99%
“…No hypoglycemia was noticed. Until now, the largest case series (63 recipients who had received Dulaglutide regardless of the time of onset of diabetes with respect to a transplant) to be reported was published in 2018 [65]. The baseline renal function was good, 1.55 mg/dL of Scr.…”
Section: Glp-1r For Recipientsmentioning
confidence: 99%